Optimization of Diclofenac Treatment in Synthetic Wastewater using Catalytic Ozonation with Calcium Peroxide as Catalyst: 10.32526/ennrj/22/20240102 - Chookaew, Papitchaya; Sukmilin, Apiradee; Jarusutthirak, Chalor (Environment and Natural Resources Journal, 2024)
This research studied the performance of ozonation process combined with calcium peroxide (CaO2) as a catalyst for the removal of diclofenac (DCF) from synthetic wastewater. The experiments were conducted using venturi-type ozonation with an ozone production rate of 96.30 mg/h. Response surface methodology (RSM) with a Box-Behnken experimental design (BBD) was used to investigate the DCF removal efficiency by optimizing the catalytic ozonation process and analyzing the influence of key parameters: solution pH (5.0-9.0), initial DCF concentration (10-25 mg/L), CaO2 dosage (1-3 g/L), and reaction time (30-90 min), on the DCF removal efficiencies. Analysis of variance (ANOVA) indicated that the experimental model derived from the RSM-BBD was best suited to a quadratic regression model, with a coefficient of determination (R2) of 0.84. The model demonstrated that the optimal conditions for achieving the highest DCF removal efficiency of up to 100% were an initial DCF concentration of 10 mg/L, solution pH of 7, CaO2 dosage of 2 g/L, and reaction time of 90 min. Using these conditions, the actual DCF removal efficiency from a confirmation test was 97.6%. The accuracy of the model was verified; the root mean square error (RMSE) was 5.90 and the mean absolute percentage error (MAPE) was 6.10%, indicating that the regression model could be used to predict the DCF removal efficiency under various conditions. The results showed that catalytic ozonation using CaO2 as a catalyst could effectively remove DCF in synthetic wastewater.